Sistema web para lojas de aluguel e venda de roupas - Kist, Cássyo Junior Rebonato (2012)
The web applications provide easy access for users because the basic requirement to access these applications is a computer with Internet access and a web browser installed. This type of application is also useful for companies that have branches. With use of the Internet there is no need for a dedicated network to connect computers and array of subsidiaries. Considering this context, it was found that the development of a web-based system could be relevant to the management of a company that rents and sells clothes and has offices. The implementation aims to show how to use the technologies employed, especially Java web and the frameworks PrimeFaces and Hibernate, and the JQuery library.